Transnational power and translocal governance: The politics of corporate responsibility - Banerjee, Subhabrata Bobby (Human relations (New York), 2018)
In this article, I provide a critical analysis of the politics of corporate social responsibility. I argue that corporate social responsibility is a strategy that enables multinational corporations to exercise power in the global political economy. Using the global extractive industries as a context, I focus on conflicts between communities, the state and multinational corporations that arise owing to the negative social and environmental impacts of mining and extraction. In particular, I analyse the role of political corporate social responsibility and multi-stakeholder initiatives in managing conflicts and argue that these initiatives cannot take into account the needs of vulnerable stakeholders. Power asymmetries between key actors in the political economy can diminish the welfare of communities impacted by extraction. Several governance challenges arise as a result of these power asymmetries and I develop a translocal governance framework from the perspective of vulnerable stakeholders that can enable a more progressive approach to societal governance of multinational corporations.